Global activism reader / edited by Luc Reydams - "Reydams, Luc. (ed.)" (New York, 2011)
Designed for undergraduate students, this reader combines essays on actual causes and issues that mobilize activists with theory and concepts of social mobilization. "The Global Activism Reader" is a unique collection of essays that introduce the various causes, actors, and organization of transnational mobilization to provide a broad, accessible survey of cases and theory. Beginning with concepts and definitions, the reader offers some historical perspective before focusing on contemporary transnational activism. This core section includes major causes or issue areas and specific campaigns. Readings on any given issue always include a critical or dissident voice. Weaving theory with case studies, the work discusses the environment, human rights, women's rights, arms control and disarmament, global justice and democracy, and religion. In addition, each essay features an introduction and conclusion by the editor as well as suggestions for further readings. The Reader addresses undergraduate students in political science and international relations in such courses as transnational activism, globalization, and global policy. It will allow students not only to learn about various contemporary movements, but also to develop a theoretical perspective to understand them.
Keywords: Civil society